L-ascorbic acid and α-tocopherol content in apple pulp: a comparison between 24 cultivars and annual variations during three harvest seasons. Issue 1 (1st January 2020) - Bianchi, Flavia; Soini, Evelyn; Ciesa, Flavio; Bortolotti, Laura; Guerra, Walter; Robatscher, Peter; Oberhuber, Michael
ABSTRACT: This study aimed to analyze the most important apple vitamin, L-ascorbic acid (AsA), and the most abundant fat-soluble one, α-tocopherol, in the pulp of 24 cultivars from harvest season 2010 and in six cultivars collected over three consecutive years (2008–2010). All cultivars were grown and stored under identical conditions and identified as 'true to type' by molecular genetic tools. The two vitamins were analyzed using high performance liquid chromatography with diode array detection (HPLC-DAD), involving two rapid methods with excellent recovery, linearity, precision, and sensitivity. Results showed an intriguing diversity of AsA contents and, to a lesser extent, of α-tocopherol in biological replicates, between cultivars and harvest years. Nevertheless, cultivar-specific relative vitamin contents can be deduced from this study. Among the 24 cultivars, a minimum AsA content of 0.43 ± 0.13 mg/100 g fresh weight (FW) and a maximum of 6.22 ± 1.06 mg/100 g FW have been found in 'Gala' and 'Freiherr von Berlepsch, ' respectively. α-tocopherol ranged from 0.13 ± 0.02 mg/100 g FW to 0.33 ± 0.04 mg/100 g FW for 'Freiherr von Berlepsch' and 'Brixner Plattling, ' respectively. The results of the present study suggest a potential of some old cultivars as a component of a healthy, vitamin-rich diet.